Wake up, Pixoto! - Weng, Pixin, 1983- (Drawn & Quarterly, 2025)
"Weng Pixin revisits herself at her most vulnerable, in her art school days. She tries on various identities trying to understand who she is. Is she a sexual libertine? A fine artist? A sensitive friend? Just then, in steps a charismatic art instructor who helps her see her true worth. She joins his tight-knit group of artistic seekers and begins her real education. But...is something sinister lurking beneath the surface? Rivalries develop, friends disappear or are cast out, her instructor's words take on a caustic edge. Pix becomes unmoored and less sure of herself than ever before and she begins to suspect she's entered into a cult."--Publisher.